Numerical and experimental analysis of heat and mass transfer in the drying process of the solar drying system - Das, Mehmet; Alic, Erdem; Akpinar, Ebru Kavak (Elsevier - Division Reed Elsevier India Pvt Ltd, 2021)
Design in a solar food drying system is crucial for food drying performance. In order to make effective use of the sun, the use of air-heated solar collectors is gradually increasing in drying systems. Dryer room temperature and pressure distribution modelling is a very important factor for system design and product selection. In this study, the drying air speed, drying temperature, and product moisture content values of a solar drying system were numerically modelled in a time dependent manner. In numerical analysis, temperature and drying air velocity were defined as variable under initial and boundary conditions. Polynomial equations based on time obtained from drying room inlet temperature and drying air velocity data were used. The R-2 values of these equations were calculated as 0.96 and 0.91, respectively. COMSOL multiphysics program was used for temperature values, drying air velocity, product moisture content values and drying chamber pressure values modelling. Depending on the position of the sun and the time, the drying chamber inlet temperature values and air velocity values have been change. During the drying process of the product, moisture content values, heat and mass transfer values, drying efficiency values, diffusion coefficient and activation energy values were examined. Experimental data and computed fluid dynamics analysis (CFD) data were compared. Using the CFD numerical analysis program, the drying room temperature, moisture content and air velocity values were modelled with mean absolute percent error (MAPE) of 5.34%, 3.74% and 6.30%, respectively. (C) 2020 Karabuk University. Publishing services by Elsevier B.V.
Keywords: Solar energy; CFD; Heat and mass transfer; Drying efficiency